Rickettsial Infections among Cats and Cat Fleas in Riverside County, California - Mullins, Kristin E. (Am J Trop Med Hyg, 2018)
Presently, few studies have investigated the role of domestic cats (Felis catus) in the recrudescence of flea-borne rickettsioses in California and the southern United States. In this study, we aimed to investigate the presence of Rickettsia typhi or Rickettisa felis in domestic cats (F. catus) and the fleas (primarily Ctenocephalides felis, the cat flea) associated with these cats in Riverside County, California. Thirty cats and 64 pools of fleas collected from these cats were investigated for rickettsial infections. Three cats and 17 flea pools (from 10 cats) tested positive for rickettsial infections. polymerase chain reaction and DNA sequencing indicated that one of the cats was positive for R. felis infections, whereas two were positive for Candidatus Rickettsia senegalensis infection. In addition, 12 of the flea pools were positive for R. felis, whereas five were positive for Ca. R. senegalensis. By contrast, no cats or their associated fleas tested positive for R. typhi. Finally, eight sera from these cats contained spotted fever group Rickettsia (SFGR) antibodies. The detection of R. felis and SFGR antibodies and the lack of R. typhi and TGR antibodies support R. felis as the main rickettsial species infecting cat fleas. The detection of Ca. R. senegalensis in both fleas and cats also provides additional evidence that cats and their associated fleas are infected with other R. felis–like organisms highlighting the potential risk for human infections with R. felis or R. felis–like organisms.